Are there three main subgroups within the patellofemoral pain population? A detailed characterisation study of 127 patients to help develop targeted intervention (TIPPs). Issue 14 (1st February 2016) - Selfe, James; Janssen, Jessie; Callaghan, Michael; Witvrouw, Erik; Sutton, Chris; Richards, Jim; Stokes, Maria; Martin, Denis; Dixon, John; Hogarth, Russell; Baltzopoulos, Vasilios; Ritchie, Elizabeth; et al.
Abstract : Background: Current multimodal approaches for the management of non-specific patellofemoral pain are not optimal, however, targeted intervention for subgroups could improve patient outcomes. This study explores whether subgrouping of non-specific patellofemoral pain patients, using a series of low cost simple clinical tests, is possible. Method: The exclusivity and clinical importance of potential subgroups was assessed by applying à priori test thresholds (1 SD) from seven clinical tests in a sample of adult patients with non-specific patellofemoral pain. Hierarchical clustering and latent profile analysis, were used to gain additional insights into subgroups using data from the same clinical tests. Results: 130 participants were recruited, 127 had complete data: 84 (66%) female, mean age 26 years (SD 5.7) and mean body mass index 25.4 (SD 5.83), median (IQR) time between onset of pain and assessment was 24 (7–60) months. Potential subgroups defined by the à priori test thresholds were not mutually exclusive and patients frequently fell into multiple subgroups. Using hierarchical clustering and latent profile analysis three subgroups were identified using 6 of the 7 clinical tests. These subgroups were given the following nomenclature: (1) 'strong', (2) 'weak and tighter' and (3) 'weak and pronated foot'. Conclusions: We conclude that three subgroups of patellofemoral patients may exist based on the results of six clinical tests which are feasible to perform in routine clinical practice. Further research is needed to validate these findings in other data sets and, if supported by external validation, to see if targeted interventions for these subgroups improve patient outcomes.